The negative aspects of injury on motivation of sports and physical exercise practitioners - Machado, Hugo Enrico Souza; Oliveira, Andreza do Socorro Dantas; Souza da Cunha Júnior, Eldimberg; Lemos, Adriano Lopes; Penna, Eduardo Macedo; Pires, Daniel Alvarez (Frontiers in Psychology, 2025)
IntroductionInjury is an inherent situation in the sports and recreational environment of physical exercise practices. Additionally, injured practitioners might present different motivational drives that may impair the continuity in physical exercise. However, little is known about the motivational profile of injured physical exercise practitioners. The aim of this study is to describe and compare different dimensions of motivation among injured (IG) and non-injured (NIG) physical exercise and sport practitioners.MethodsA total of 83 participants made part of the study (IG: 52, age: 30.8 ± 8.4 years; NIG: 31, age: 27.5 ± 8.4 years). An ad hoc on-line questionnaire was used, containing sociodemographic information and the Sport Motivation Scale (SMS-II). The SMS-II evaluates different dimensions of motivation based on the tenets of the self-determination theory and was answered by both groups to examine possible differences. The researchers contacted clubs and gyms, as well as online promotions.ResultsIn the IG, there was a prevalence of 45% of give-up thoughts and 48% were competing. Also, the IG demonstrated higher median values of demotivation when compared to the NIG, with a small effect size (NIG median: 3.3; IG median: 5.8; p = 0.04, r = 0.26).ConclusionWe conclude that almost half of the injured practitioners demonstrated give-up thoughts as well as exhibit higher levels of demotivation compared to non-injured ones. Thus, it indicates the need for a rehabilitation approach also focused on motivational issues, to improve overall heath and prevent physical activity drop out.